A fluorescence‐based yeast sensor for monitoring acetic acid. Issue 5 (18th January 2021) - Hahne, Katja; Rödel, Gerhard; Ostermann, Kai
Abstract: Accumulation of acetic acid indicates an imbalance of the process due to a disturbed composition of the microorganisms. Hence, monitoring the acetic acid concentration is an important parameter to control the biogas process. Here, we describe the generation and validation of a fluorescence‐based whole cell sensor for the detection of acetic acid based on the yeast Saccharomyces cerevisiae . Acetic acid induces the transcription of a subset of genes. The 5´‐regulatory sequences (5´ URS) of these genes were cloned into a multicopy plasmid to drive the expression of a red fluorescent reporter gene. The 5´ URS of YGP1, encoding a cell wall‐related glycoprotein, led to a 20‐fold increase of fluorescence upon addition of 30 mM acetic acid to the media. We show that the system allows estimating the approximate concentration of acetic acid in condensation samples from a biogas plant. To avoid plasmid loss and increase the long‐term stability of the sensor, we integrated the reporter construct into the yeast genome and tested the suitability of spores for long‐term storage of sensor cells. Lowering the reporter gene's copy number resulted in a significant drop of the fluorescence, which can be compensated by applying a yeast pheromone‐based signal amplification system.